Nuclear terrorism countering the threat - Volders, Brecht; Sauer, Tom (Routledge global security studies, 2016)
Nuclear terrorism is perceived as one of the most immediate and extreme threats to global security today. The volume aims to do this by investigating the different types of nuclear terrorism, and subsequently discussing the potential means to prevent these malicious acts. In addition, there is a discussion of the nuclear security regime, in general, and an important examination of both its strengths and weaknesses. This book will be of much interest to students of nuclear proliferation, nuclear governance, terrorism studies, international organizations, and security studies in general.